Determining Factors in Implementing Accounting Conservatism: A Study of Technology and Health Companies in Indonesia - Nurcahyadi, Khafid; Yuliati (Shafin: Sharia Finance and Accounting Journal, 2025)
Recently, various kinds of corporate fraud scandals have become increasingly common. Financial reports, which should be prepared to be a communication tool for management to stakeholders, have instead become a tool for management to gain intensity with undue recognition for personal interests. This can make stakeholders make mistakes in making decisions and projecting the future. It is necessary to have more conservative principles to be able to minimize management’s opportunistic behavior and also maintain business continuity. The method used in this research is a descriptive method with quantitative data types. The population in this study is 81 companies in the technology and health sectors listed on the Indonesia Stock Exchange in 2021-2023, with a sample size of 39 representative companies. The data collection technique used was observation using a panel data regression test. Earning pressure, debt covenant, and investment opportunity set simultaneously have a significant effect on accounting conservatism. Earning pressure has a significant positive effect on accounting conservatism. Debt covenants have a significant positive effect on accounting conservatism. Investment opportunity set has a significant negative effect on accounting conservatism. This research aim to help investors and stakeholders in assessing company financial reports as a decision-making tool. It is also hoped that this study can help companies understand the application of accounting conservatism principles to companies.